Effectiveness and safety of interventions to manage childhood overweight and obesity: An Overview of Cochrane systematic reviews. Issue 5 (20th August 2020) - Gates, Allison; Elliott, Sarah A; Shulhan-Kilroy, Jocelyn; Ball, Geoff D C; Hartling, Lisa
Abstract: Background: Childhood overweight and obesity are associated with adverse physical, social, and psychological outcomes. Objectives: We conducted an overview of Cochrane systematic reviews on the effectiveness and risks of interventions to treat overweight and obesity in children and adolescents. Methods: In June 2019, we searched the Cochrane Database of Systematic Reviews for eligible reviews. The primary outcomes were change in adiposity (body mass and body mass index [BMI] z-score) and adverse events. Two reviewers screened studies and one reviewer extracted and another verified data. Two reviewers assessed methodological quality and reached consensus. Data were synthesized narratively. Results: We included seven Cochrane reviews published between 2011 and 2017 containing evidence from 167 randomized controlled trials with 21, 050 participants. Lifestyle and behavioural interventions more effectively reduced weight compared with no intervention, usual care, or another behavioural treatment (three reviews, low-to-moderate certainty). Parent–child lifestyle and behavioural interventions more effectively reduced BMI z-score compared with no intervention (one review, low certainty). Decision support tools for healthcare providers more effectively limited increases in BMI z-score compared with usual care (one review, moderate certainty). Pharmacologic treatments combined with behavioural modification more effectively reduced adiposity compared with placebo or usual care (one review, low certainty), but the risk of adverse events was greater than non-pharmacologic therapy. Surgical interventions (e.g., LAP-BAND) combined with behavioural modification more effectively reduced adiposity compared with behavioural modification alone (one review, low certainty). Those who underwent surgery reported a higher number of adverse events compared with those treated with lifestyle modification. Conclusions: There is low-certainty evidence that lifestyle and behavioural interventions, pharmacologic interventions, and surgical interventions are effective in weight management for children with overweight and obesity. Safety data remain lacking across all intervention modalities. Future research should focus on implementation strategies. Further, a focus on overall well-being may be more beneficial than weight management specifically.